Axiomatics of the poetic supertextual units - Hakobyan, Levon (Bulletin of Yerevan University H: Russian Philology, 2022)
The article presents the substantiation of the term "poetic supertextual unit" introduced by the author to denote an integrative concept that combines such forms of organization of poetic texts as a crown of sonnets, a lyric cycle and a book of poems.First of all, the fundamental difference between this term and the adjacent concept of “supertext”, which is a set of thematically related texts created at different times by different authors, is determined.For the explication of the concept of "supertextual unit" the method of step-by-step expansion of the semantics of the term is used. The main parameters of the supertextual unit, which characterize each of the named forms into an integral unit, are identified and studied in detail.A preliminary study made it possible to identify the most significant parameters of the supertextual unit. These parameters are stable, although with varying intensity, in the crown of sonnets, the lyrical cycle and the book of poems. These are: a closed set of texts, a common title, orderliness, interconnectedness, complementarity.The last three parameters determine the cohesion of the supertextual unit, which is not identical to the intratext cohesion. The intratextual coherence is provided mainly by the syntagmatic expansion of the text. The cross-textual connections are manifested mainly in the paradigmatic comparison and opposition of the semantic systems of the components of the supertextual unit due to the presence of multilevel cross-textual repetitions that ensure the emergence of structural, associative and connotative links between texts. Paradigmatic connections predetermine the emergence of semantic tension between texts, as a result of which new meanings are generated.
Keywords: poetic supertextual unit; crown of sonnets; lyric cycle; book of poems; parameters; orderliness; interconnectedness; complementarity